Electrophysiological measurement of ion channels on plasma/organelle membranes using an on-chip lipid bilayer system. Issue 1 (December 2018) - Kamiya, Koki; Osaki, Toshihisa; Nakao, Kenji; Kawano, Ryuji; Fujii, Satoshi; Misawa, Nobuo; Hayakawa, Masatoshi; Takeuchi, Shoji
Abstract Ion channels are located in plasma membranes as well as on mitochondrial, lysosomal, and endoplasmic reticulum membranes. They play a critical role in physiology and drug targeting. It is particularly challenging to measure the current mediated by ion channels in the lysosomal and the endoplasmic reticulum membranes using the conventional patch clamp method. In this study, we show that our proposed device is applicable for an electrophysiological measurement of various types of ion channel in plasma and organelle membranes. We designed an on-chip device that can form multiple electrical contacts with a measurement system when placed on a mount system. Using crude cell membranes containing ion channels extracted from cultured cells without detergents, we detected open/close signals of the hERG, TRPV1, and NMDA channels on plasma membranes, those of the TRPML1 channels on lysosomal membranes, and open/close signals of the RyR channels on SR membranes. This method will provide a highly versatile drug screening system for ion channels expressed by various cell membranes, including plasma, SR, mitochondrial, Golgi, and lysosomal membranes.